PERAN MODERASI DISIPLIN KERJA PADA PENGARUH KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PERBANKAN SYARIAH DI MAKASSAR - Edy Jumady (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2020)
This study aims to examine the influence of leadership on employees work activity moderated work discipline at Islamic banking in Makassar. Data collection uses the primary data obtained from questionnaires using technitk proportionated random sampling. The population is all 162 permanent employees from 11 Islamic banks in Makassar City, while the sample taken is 62 respondents. The results of the questionnaire have been tested for validity and reliability. Methoddata analysis using SEM technique (Sturctural equation modeling) assisted with WarphPLS Ver.5.0. The results of this study indicate that the hypothesis of leadership is accepted in part because it shows the result of hypothesis test that negative and significant. This means that influential negative leadership and significant to employees work activity. then result research on work discipline shows that the hypothesis is accepted because it shows results a positive and significant hypothesis. this means that positive discipline work is positive and significant to employees work activity. While the results of research on discipline work as the strengthening variable indicates that the hypothesis is accepted as it shows the results a positive and significant hypothesis. This means that the work discipline variable can strengthen variable leadership on employees work activity. Keywords: Leadership, Work Discipline, Employee Performance, Islamic Banking